Designing differential pressure leggings for late middle age women using 3D technology: Identifying optimal muscle support levels via electromyography - Nam Yim Kim; Hyojeong Lee (Journal of Engineered Fibers and Fabrics)
This study aims to identify appropriate pressure levels for supporting key thigh muscles in late middle age women by analyzing muscle fatigue responses using surface electromyography (EMG). Functional leggings were developed for Korean women in their 50s using 3D human body data, focusing on targeted reinforcement of the vastus medialis and vastus lateralis within the quadriceps femoris. Leggings patterns were created with region-specific reduction rates derived from preliminary evaluations and virtual simulations. The final garments were assessed through quantitative clothing pressure measurements, EMG-based muscle fatigue analysis, and subjective comfort evaluation. Results showed that clothing pressure was lowest at the waist and highest at the back of the calf, ranging from 0.77 to 1.98 kPa. Notably, muscle fatigue in the vastus medialis and vastus lateralis significantly decreased when wearing the leggings compared to loose-fit control pants. Furthermore, reductions exceeding 20% were observed in the vastus medialis and biceps femoris. Subjective evaluations indicated high satisfaction across all items, particularly in muscle support and suitability for exercise. These findings suggest that the developed leggings apply optimal pressure to key muscle areas, effectively reduce fatigue, and offer a comfortable and supportive option for activewear among late middle age women.